2-Aminobenzoyl and megastigmane glycosides from Wrightia antidysenterica. (February 2019) - Srinroch, Chutima; Sahakitpichan, Poolsak; Techasakul, Supanna; Chimnoi, Nitirat; Ruchirawat, Somsak; Kanchanapoom, Tripetch
Graphical abstract: 2-Aminobenzoyl O -β-D-apiofuranosyl-(1→6)-β-D-glucopyranoside (1 ) along with wrightiaionosides A (10 ) and B (11 ) were isolated from Wrightia antidysenterica . Highlights: 2-Aminobenzoyl diglycoside was isolated from Wrightia antidysenterica . Two new megastigmane glycosides were obtained from Wrightia antidysenterica. Benzoxazinoids were obtained from Wrightia antidysenterica of the family Apocynaceae. Abstract: A new aminobenzoyl glycoside, 2-aminobenzoyl O -β-D-apiofuranosyl-(1→6)-β-D-glucopyranoside (1 ) and two new megastigmane glycosides, wrightiaionosides A (10 ), and B (11 ), were isolated along with 17 known compounds, including four benzoxazinoid glycosides (2-5 ), one indole diglycoside (6 ), three simple aromatic glycosides (7-9 ), three megastigmane glycosides (12-14 ), five flavonoid glycosides (15-19 ) and one lignan (20 ). The structure elucidation of these compounds was based on analyses of physical and spectroscopical data including 1D and 2D NMR experiments.